MoS2 nanosheets decorated with gold nanoparticles for rechargeable Li–O2 batteries1. Issue 28 (28th July 2015) - Zhang, Panpan; Lu, Xueyi; Huang, Ying; Deng, Junwen; Zhang, Lin; Ding, Fei; Su, Zhiqiang; Wei, Gang; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> MoS2 nanosheets decorated with gold nanoparticles show enhanced specific capacity and cycle efficiency for rechargeable Li–O2 batteries.